Position-specific 13C distributions within propane from experiments and natural gas samples. (1st January 2018) - Piasecki, Alison; Sessions, Alex; Lawson, Michael; Ferreira, A.A.; Santos Neto, E.V.; Ellis, Geoffrey S.; Lewan, Michael D.; Eiler, John M.
Abstract: Site-specific carbon isotope measurements of organic compounds potentially recover information that is lost in a conventional, 'bulk' isotopic analysis. Such measurements are useful because isotopically fractionating processes may have distinct effects at different molecular sites, and thermodynamically equilibrated populations of molecules tend to concentrate heavy isotopes in one molecular site versus another. Most recent studies of site-specific 13 C in organics use specialized Nuclear Magnetic Resonance (NMR) techniques or complex chemical degradations prior to mass spectrometric measurements. Herein we present the first application of a new mass spectrometric technique that reconstructs the site-specific carbon isotope composition of propane based on measurements of the 13 C/ 12 C ratios of two or more fragment ions that sample different proportions of the terminal and central carbon sites. We apply this method to propane from laboratory experiments and natural gas samples to explore the relationships between site-specific carbon isotope composition, full-molecular δ 13 C, thermal maturity, and variation in organic matter precursors. Our goal is to advance the understanding of the sources and histories of short-chain alkanes within geologic systems. Our findings suggest that propane varies in its site-specific carbon isotope structure, which is correlated with increasing thermal maturity, first increasing in terminal position δ 13 C and then increasing in both center and terminal position δ 13 C. This pattern is observed in both experimental and natural samples, and is plausibly explained by a combination of site-specific, temperature-dependent isotope effects associated with conversion of different precursor molecules (kerogen, bitumen, and/or oil) to propane, differences in site-specific isotopic contents of those precursors, and possibly distillation of reactive components of those precursors with increasing maturity. We hypothesize that the largest changes in site-specific isotopic content of propane occur when bitumen and/or oil replace kerogen as the dominant precursors. If correct, this phenomenon could have significant utility for understanding gas generation in thermogenic petroleum systems.